The factors of contribution of the higher number of local employees’ lateness and absenteeism at MCIS Safety Glass Sdn Bhd / Siti Nur Aaisyah Alias - Alias, Siti Nur Aaisyah (2013)
The purpose of this study is to determine “The Factors of Contribution of the Higher Number of Local Employees’ Lateness and Absenteeism at MCIS Safety Glass SDN BHD”. For this study only 125 respondents out of the population at MCIS Safety Glass SDN BHD were selected and act as a respondent for this study. The objective of thesis study is to study the factors of contribution of the higher number of local employees’ of lateness and absenteeism at MCIS Safety Glass SDN BHD, to find any significant relationship between the factors of the contribution of lateness and absenteeism and the higher number of local employees’ lateness and absenteeism at MCIS Safety Glass SDN BHD and to examine the most factors of the contribution of lateness and absenteeism towards the higher number of lateness and absenteeism among local employees’ at MCIS Safety Glass SDN BHD? Besides that, this study is quantitative research whereby the findings of the study were analyzed by using the Statistical Package for the social science (SPSS). Moreover, the data collection in this study is analyzed by using frequency, descriptive analysis, reliability, and Pearson’s Correlation analysis and regression analysis in order to achieve the research objective. Eventually, this study discovered that most of the respondents were agreed to the information to be asking about the factors of the contribution of the lateness and absenteeism. Furthermore, the researcher does the measurement of central tendency and dispersion to determine the frequency, mean, mode, median, variance and standard deviation for each independent variables. By doing the measurement, the research objectives are successfully answered. There also have a recommendation topic to further the studies about the employee lateness and absenteeism to emphasize to personal Human Resource course to school and educational institutions.